The stone lamp : eight stories of Hanukkah through history - Hesse, Karen; Pinkney, J. Brian (New York : Hyperion Books for Children, 2003)
A collection of eight poems, each taking place on a different night of Hanukkah and following the history of Jews from twelfth-century England to twentieth-century Israel.
Keywords: Hanukkah -- Juvenile poetry; Judaism -- Juvenile poetry; Children$1 (Bs poetry, American.s; Jews -- History -- Poetry; Hanukkah -- Poetry; American poetry